Działania na rzecz aktywizacji osób poszukujących pracy na rynku pracy w Polsce - Sobocka-Szczapa, Halina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The objective of this study is to show the situation on a scale of applied active labour market policy's tools in Poland. It especially presents an analysis of the effectiveness of the chosen tools. Among them are courses led by public employment services. Due to the obligatory law, these courses should not only contribute to the strengthening of the competitive position of people seeking a job on local labour markets, but also help these people in adjusting their qualifications to the employers' needs. And in this way exactly, one can understand the influence of these activities on the intellectual potential of the unemployed people and consequently their direct influence on reducing disproportions - especially the structural ones - on the labour market. Those activities should be submitted to the most important challenges, pointed out by the labour market strategy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 475-494